Measurement and Dynamic Change Analysis of Total Factor Productivity of China′s Marine Economy: Based on DEA Malmquist index model - Yaozong WANG (Haiyang Kaifa yu guanli, 2022)
By selecting marine economic development indicators and using DEA Malmquist index model to calculate the total factor productivity of marine economic development in 11 coastal areas of China from 2006 to 2018, this paper discussed the time series changes and sources of changes in total factor productivity of marine economic development, and further divided different regions for heterogeneity analysis. The research results showed that China′s marine economy had a good momentum of development, and the improvement of total factor productivity had increased by 4.811% on average during the study period. The main reason for the improvement was the progress of technical level, while the contribution of technical efficiency level was small. Due to different internal and external conditions in different provinces, the improvement of TFP in different provinces varied greatly. On the whole, the performance of southern provinces was better than that of northern provinces, the improvement of total factor productivity in the southern marine economic circle was the highest, followed by the eastern marine economic circle, and the northern marine economic circle was the worst.